Study on the Effect of Elevators in the Vertical Plane on the Motion Performance of a Twin Hybrid Autonomous Underwater Vehicle by Simulation - Jiafeng Huang; Kele Zhou; Hyeung-Sik Choi; Ruochen Zhang; Phan Huy Nam Anh; Dong-Wook Jung; Mai The Vu (Journal of Marine Science and Engineering, 2025)
The Twin Hybrid Autonomous Underwater Vehicle (THAUV) is an underwater monitoring system consisting of a twin buoyant body and a fixed wing mounted between them. It is equipped with two propeller thrusters and a pair of elevators at the aft end. As a new type of underwater vehicle, it combines the long endurance of an underwater glider (UG), the high-speed maneuverability of an autonomous underwater vehicle (AUV), and the ability to carry larger payloads. In this paper, the motion equations of the THAUV are established, and its simulation model is developed using SIMULINK. Computational fluid dynamics (CFD) is further employed to identify hydrodynamic parameters under different elevator size conditions. A case study is conducted to analyze the effects of three different widths of elevators on glide performance, including gliding speed, pitching angle, and gliding trajectory. CFD results show that when the elevator deflection angle is zero, the hydrodynamic forces acting on the THAUV increase as the elevator width increases under identical angle of attack and velocity conditions. Under CFD conditions with fixed angle of attack and flow velocity, the sensitivity of the hydrodynamic characteristics to elevator deflection became significantly more pronounced. Increasing the elevator deflection angle led to substantial growth in the generated hydrodynamic forces. Motion simulations further show that increasing the elevator deflection angle enhances the THAUV’s gliding performance. Comparative results also reveal that glide performance improves with larger elevator width.

Removal of 48 per- and polyfluoroalkyl substances (PFAS) throughout processes in domestic and general industrial wastewater treatment plants: Implications for emerging alternatives risk control - Yueqing Zhang; Ruochen Dong; Feng Ge; Minghui Hong; Zhanghao Chen; Yunqiao Zhou; Jing Wei; Cheng Gu; Deyang Kong (Journal of Hazardous Materials, 2024)

Emerging and legacy per- and polyfluoroalkyl substances (PFAS) in fluorochemical wastewater along full-scale treatment processes: Source, fate, and ecological risk - Yueqing Zhang; Yunqiao Zhou; Ruochen Dong; Ninghui Song; Minghui Hong; Juying Li; Jia Yu; Deyang Kong (Journal of Hazardous Materials, 2024)

Self-Assembled FeIII-TAML-Based Magnetic Nanostructures for Rapid and Sustainable Destruction of Bisphenol A - Ruochen Dong; Lihua Bai; Sijia Liang; Shuxia Xu; Song Gao; Hongjian Li; Ran Hong; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2024)

One-step processing of waste dredged slurry into planting soil by targeted pretreatment and vacuum filtration - Silin Wu; Xiao Peng; Xiaohui Sun; Zijun Dong; Aizhao Zhou; Lei Zhang; Ruochen Wang (Journal of Environmental Management, 2024)

Multi-layer multi-objective cooperative regulation of agricultural water resources in large agricultural irrigation areas based on runoff prediction - Mo Li; Wuyuan Liu; Qiang Fu; Dong Liu; Tianxiao Li; Yaowen Xu; Ruochen Shang (Computers and Electronics in Agriculture, 2023)

Study on Position and Shape Effect of the Wings on Motion of Underwater Gliders - Jiafeng Huang; Hyeung-Sik Choi; Mai The Vu; Dong-Wook Jung; Ki-Beom Choo; Hyun-Joon Cho; Phan Huy Nam Anh; Ruochen Zhang; Jung-Hyeun Park; Joon-Young Kim; Huy Ngoc Tran (Journal of Marine Science and Engineering, 2022)
A typical structure of an underwater glider (UG) includes a pair of fixed wings, and the hydrodynamic force driving the glider forward as descending or ascending in the water is generated primarily by the fixed wings. In this paper, a simplified glider motion model was established to analyze the dynamics in an easier way, and whose simulation results do not differ from the original one. Also, in the paper, the effects of the wing position and wing shape on the UG to the motion were studied. Since no direct analytic approach cannot be performed, the case study of the effects of six different wing positions and three wing shapes on gliding performances which are gliding speed, gliding angle and gliding path were performed through computer simulation. The simulation results revealed that when the fixed wing is located far from the buoyancy center to the tail end, more traveling range is achieved with less energy. Also, effect of the shape difference of the wings were analyzed. Shape changes did not show much difference on the travelling performance of the UG. In addition to these, the transient mode of the UG was studied. To control this, the PID controller for the position of the mass shifter and piston were applied. By application of the PID controller to the linearized dynamics equations, it was shown that the transient behavior of the UG was quickly and steadily controlled.